Anxiety and depression in inflammatory eye disease: exploring the potential impact of topical treatment frequency as a putative psychometric item - Philip I Murray; James Hodson; Saaeha Rauz; Paolo Scollo; Georgios Vakros (BMJ Open Ophthalmology)
Objective To evaluate whether topical therapy is linked to scores related to anxiety, depression and quality of life (QoL) in inflammatory eye disease (IED).Methods and analysis Patients with ocular surface disease (OSD, N=100) and Uveitis (N=100) completed self-administered validated questions on ocular symptoms and well-being, with supplemental questions on eye drop frequency.Results Forty (20%) patients had scores consistent with depression and 33 (17%) anxiety. Anxiety, depression, QoL and OSD index (OSDI) scores did not differ significantly between OSD and Uveitis groups. In those with anxiety or depression, QoL was significantly reduced in all WHO Quality Of Life-BREF domains (all p<0.001). Multivariable analysis considering demographic and disease-related factors found daily topical drop frequency to be independently associated with anxiety (p=0.009) but not depression (p=0.300).Conclusion A high proportion of patients with IED demonstrated scores indicative of anxiety and depression. Preliminary evidence suggests that the frequency of topical eye drops potentially plays a significant role in the psychological health status of patients with IED .